An Analytical Study of Asad Muhammad Khan’s Representative Short Stories - Kallu, Parveen; khan, Arbab; Khan, Javez (sourcecoder, 2024)
Asad Mohammad Khan has a deep experience of diverse life, an awareness of human nature and an immense capacity for expression as well as a willingness to find new artistic resources and techniques to describe the complex reality enveloped by history, imagination and contemporary life. There is hope. His fame in the world of fiction became from the first collection "Khirrki Bhar Aasman" which included thirteen 13 fables along with thirty eight 38 poems, but included in this collection "Basoday Ki Maryam", "Mai Dada" and "Tirlochan" were such legends that have earned a place in Urdu epics. These three characters are fiction. In which family members (parents) with a feudal background have been made more noble and there is this reference of pride for Mutkalam that great values and attitudes are involved in his training. "Maryam", and "May Dada" will be extraordinary characters, which are deeply influenced by Asad Muhammad Khan’s characterization, atmosphere and dialogue. "Basoday Ki Maryam"is an unparalleled addition to Urdu fiction literature. Tarlochan is an ideal idea for the creative treatment of the sufferings of the slums and slums of Karachi. The authorities of Ashfaq Ahmad, Qudratullah Shahab or Mumtaz Mufti are different in color, so "Ghos pheitiya", "Chakar","Shahr e kofay ka Mehz Aik admi", "Ghussay ki Nai Fasl" and Those stories which have been mentioned earlier have a deep meaning and emotional depth due to this experience.